ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN METODE KONTRASEPSI IUD DIPUSKESMAS KECAMATAN MENTENG JAKARTA PUSAT - Dortea Lewen (STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2021)
Contraception comes from the word con which means 'to prevent' or 'against' and conception which means the meeting between a mature egg cell and a sperm cell which results in pregnancy. This study aims to determine the factors that influence the selection of the IUD contraceptive method at the Menteng District Health Center, Central Jakarta in 2017, with a sample of 51 respondents. The research design used in this research is a descriptive research design using simple random sampling technique. The results of the study were seen from the age of 20-35 years as many as 30 people (59.0%), acceptors with age> 35 years as many as 21 people (41.0). Elementary education was 5 respondents (10.0%), Middle school was 11 respondents (22.0%), SMA was 20 respondents (39.0%), University was 15 respondents (29.0%). Lack of knowledge 40-55% as many as 4 people (8.0%), sufficient knowledge 56-75% as many as 17 people (33.0%), Good knowledge 76-100% as many as 30 people (59.0%). Obtained approval as many as 41 people (80.0%). Getting information from Health Officers as many as 29 people (57.0%), getting information from Electronic Print Media as many as 18 people (35.0%), and getting information from neighbors and family members as many as 4 people (8.0%). The culture does not support as many as 8 people (16.0%), acceptors whose culture supports as many as 43 people (84.0%). And for those who do not believe as many as 12 people (23.0%), acceptors who believe as many as 39 people (77.0%).